Hubungan Potensi Interaksi Obat Antihipertensi terhadap Luaran Klinis Pasien Lansia - Ayu Waningsih; Lutfi Hidiyaningtyas; Novia Ariani Dewi (JOURNAL OF PHARMACEUTICAL (JOP), 2025)
Background: The prevalence of hypertension increases with advancing age. Data from the 2018 Indonesian Basic Health Research (Riskesdas) indicates that hypertension is a common condition among the elderly. Physiological changes, along with alterations in pharmacokinetics, pharmacodynamics, and a higher likelihood of comorbidities, contribute to an increased number of medications consumed by elderly patients. This condition may raise the risk of drug interactions, potentially affecting clinical outcomes. Objective: To determine the association between the potential for antihypertensive drug interactions and clinical outcomes in elderly patients. Methods: This study was an analytical observational study with a retrospective design and purposive sampling technique. A total of 92 patients were included in the study. The research was conducted in the outpatient department of a hospital in Yogyakarta using medical record data from elderly hypertensive outpatients. Drug interactions were analyzed using the drugs.com application, and the association between potential antihypertensive drug interactions and clinical outcomes was analyzed using the chi-square test. Results: Most elderly hypertensive patients were female (65.2%) and had comorbidities or complications (78.3%). The majority of patients received combination therapy (65.2%). Potential drug interactions were identified in 78.3% of patients, with 80.5% classified as moderate in severity and 80.5% involving pharmacodynamic mechanisms. The chi-square test showed a p-value of 0.445, indicating no significant association between the potential for antihypertensive drug interactions and clinical outcomes. Conclusion: There is no significant association between the potential for antihypertensive drug interactions and clinical outcomes in elderly patients